Uji Kelayakan Modul IPA Terpadu Berbasis Etnosains Pembuatan Petis Madura Tema Pemisahan Campuran - Rahman, Kholilulr; Hadi, Wiwin Puspita; Hidayati, Yunin; Muharami, Laila Khamsatul; Putera, Dwi Bagus Rendy Astid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This development research aims to determine the feasibility, student responses and produce products for integrated science module media based on mixed separation ethnoscience themes. This research is a development research that uses the 4D development modelconsisting of(Define, Design, Develop andDisseminate).However, this development only reached the development stage. The data collection technique in this research is using a questionnaire. The results of this study indicate that the integrated IPA module based on ethnoscience of mixed separation themes that was developed is included in the criteria for use, judging from the results of media expert validation of 84.37 %, media expert reliability of 92.72, material expert validation of 89.17 %, material expert reliability as big as 96.19 %. These results get a positive response so that it can be said that the integrated science module based on ethnoscience with mixed separation themes is suitable for use by seventh grade junior high school students.